Study of Lipid Profile in Pediatric Nephrotic Syndrome Patients in Karbala - Al-Foraty, Fatimah A. H; Al -Daamy, Alaa A. H.; Al-Obaidy, Qahtan M. (Scientific Journal of Medical Research, 2022)
Objective: This study aims to study detect relationship between some biological and biochemical parameters in pediatric nephrotic syndrome with different ages. Methods: The study was done between October 2021 and May 2022. In the Pediatric teaching hospital Center for Nephrology /Karbala Health Directorate. A 5 mL sample of venous blood was collected from 116 Nephrotic syndrome children patients and 42 healthy children. There are several analyses have been performed as a result, including biochemical parameters: Lipid profiles (TC, LDL, HDL, and TG), Albumin, Hematological parameters CBC, Physiological parameters (Glucose, ABO), General Parameters (Age, Weight, Gender). Results: The results show that the value of TC, LDL, HDL, TG, Albumin, and Glucose were 330.62, 204.27, 58.51, 308.67, 30.54, and 115.27 mg/dL, respectively. In children with Nephrotic syndrome there were some correlation between some parameters, such as TC and LDL (0.808) ,and TG with both LDL and TC (0.526,0.539), respectively. The B blood group in children with nephrotic syndrome was more than in healthy.